Industrial variation of high-growth firms - Sven-Olov Daunfeldt; Niklas Elert; Dan Johansson (European Regional Science Association (ERSA), 2010)
Previous examinations of the literature suggests that high-growth firms (HGFs) exist in all or most industries, are not overrepresented in high-tech, and if anything appear to be slightly overrepresented in services. In an updated overview, we find that more recent studies, employing better statistical methods, show a clear link between technological sophistication and HGFs. In a tobit model we examine what factors explain the presence of HGFs across 5-digit-NACE-industries in Sweden 1997-2005. We find that technological sophistication is crucial for the prevalence of HGFs in an industry, particularly in services. These results are in line with both current research and previous research concerning Sweden. We conclude that innovation is crucial for firm growth.
Keywords: 330; Entrepreneurship; Firm growth; Gazelles; High-growth firms; High-impact firms; Industry